Malignant Orofacial Tumors in Children and Adolescents: A Clinicopathologic Review of Cases Treated in a Teaching Hospital Northwest Nigeria - Omisakin, Olatunde Oluleke (British Journal of Healthcare and Medical Research, 2025)
Background study: Orofacial tumors in children and adolescents are relatively uncommon. Malignant variants of these tumors are rare, but they are life threatening. There are few studies on the clinico-pathological review of these malignant tumors in children and adolescents in Nigeria, therefore this review is essential to give information on the diagnosis of these tumors by dentists. Objective: To give overview of our management protocol for these tumours in North-West, Nigeria. Materials and Methods: This was a retrospective study of the children and adolescents aged ≤19 years who were presented to Barau Dikko Teaching Hospital, Kaduna, Nigeria with malignant tumors in the orofacial region. The study reviewed cases within fourteen years from January, 2009 to December, 2022. Information was extracted from patients’ case files, histopathology records and slides. Data collected includes: the age of patient at presentation, gender, location of tumor, clinical features, histopathology, treatment and complications. Results: The mean age (S.D) of patients was 11.3 (±4.9) years (range, 3.5 – 19 years). Male-to-female ratio was 1.64:1.00. The total number of patients seen during this period was 6500, of which 215 adolescents aged ≥19years had tumors and tumor-like lesion of the orofacial region. Out of these, 37 (17.22%) were malignant tumors. Sarcomas (n= 15, 40.54%) were the most common malignant tumors, followed by lymphomas (n=13, 35.13%) and then carcinomas (n=7, 18.92%), Neuroblastoma (n=2, 5.41%) was the least seen tumor. Osteosarcoma and rhabdomyosarcoma were the most common sarcomas. Carcinoma affected children in first, second decade of life; surface mucosa and glandular tissues were mostly affected. The treatments for these tumors were: surgical excision, chemotherapy and radiotherapy. Complications after treatments includes: tumor recurrence, resistant of the tumor to both chemotherapy and radiotherapy, tumor distant metastasis and death. Conclusion: Our findings established the frequent occurrence of malignant orofacial tumors in children and adolescents, with sarcomas being the most common and most life threatening in North-west, Nigeria. Further studies of these tumors would provide information and help in their diagnosis.